Julian Onderdonk in New York : the lost years, the lost paintings - Baker, James Graham, 1946- (Texas State Historical Association, 2014)
Famed for his bluebonnet landscapes, San Antonio native Julian Onderdonk may be the most well-known artist Texas has ever produced. Onderdonk spent several years outside the state, though, seeking to make a name for himself in New York City. He spent much of his time in New York as the very definition of a starving artist.In Julian Onderdonk: The Lost Years, the Lost Paintings, James Graham Baker explores the artist's New York years, so often neglected by previous scholars. Through painstaking research, Baker reveals that Onderdonk painted hundreds of images under pseud.